The unmet needs of patients with advanced incurable head and neck cancer and their carers: A systematic review and meta‐ethnography of qualitative data. (4th June 2021) - North, Alexander S.; Carson, Luke; Sharp, Linda; Patterson, Joanne; Hamilton, David W
Abstract: Introduction: Patients with advanced‐stage head and neck cancers (HNC) endure a significant symptom burden and suffer greatly towards the end of their lives. Qualitative evidence can provide insight into how existing services meet their needs. We aimed to synthesise qualitative data from patients with advanced HNC and their carers to inform improvements to services and care. Methods: A systematic search was conducted in MEDLINE and EMBASE for studies containing qualitative data from patients with advanced HNC and their carers. An interpretive account was generated using the meta‐ethnography methodology. Results: We identified 8 studies including 38 patients and 25 carers. Twenty‐six themes were synthesised into five concepts: psychological impact and adjustment, physical limitations and deliverance of symptomatic care, communication and information needs from healthcare professionals, social support and dependence, and needs of the primary caregiver. We identified that patients had complex psychological needs, centred on uncertainty and fear of suffering. Patients desired full information and found poor communication highly distressing. There was a dearth of literature on the subjective impact of physical limitations. Patients became reliant on social networks, and those with lower quality relationships coped poorly. However, caregivers struggled to meet patients' complex needs, resulting in distress and isolation. Conclusions: Patients with advanced HNCs have complex needs that are not met in current systems. Further qualitative work focusing on the physical and psychological impact of advanced HNC would be of value.